Mind Over Body Connection: Aging expectations and subjective health and well-being among older adults - Johnny Jr. Yao (ACHSM, 2022)
Background: There is credible evidence that a person's beliefs about the aging process are linked to and influence a variety of health outcomes.   Purpose: This study determined whether aging expectations predict health-related quality of life. Furthermore, the study determined whether engagement in healthy lifestyles mediates the relationship between these variables.   Methods: A descriptive-correlational study. This study enlisted a total of 95 respondents aged 60 to 85 years old in a large metropolitan area. Data were analyzed using linear regression and mediation analysis.   Results: Aging expectations and engagement in healthy lifestyles are a significant predictor of health-related quality of life (p< 0.05). Moreover, engagement in healthy lifestyles is found to be a significant mediator between the variables.   Conclusion: Older adults who have positive aging expectations and engage in health promotion activities are more likely to report better health. Therefore, programs that promote a positive aging expectation and engagement in health-promoting activities should be implemented.